Trade, investment, innovation and their impact on access to medicines : an Asian perspective / Locknie Hsu. - Hsu, Locknie (Cambridge international trade and economic law, 2016)
The last two decades have seen great economic change in Asia and this has impacted upon the vexed question of access to affordable healthcare and medicines in many Asian states. In this book Locknie Hsu examines the issue of access to medicines in Asia from a fresh perspective which embraces trade and investment law, innovation, intellectual property law, competition policy and public health issues. Hsu explores the key evolving legal issues in these areas, including ASEAN integration, free trade agreement negotiations (such as those for the TPP), bilateral investment agreements and significant court decisions. The book goes on to present proposals for steps to be taken in addressing access to medicines in Asia and will be useful to academic researchers, regulators, law-makers and global organizations involved in the issues surrounding access to affordable healthcare and medicines.